If you’re both working at a constant rate, then he would have one hour left when you go to help him. Since there are two of you, you accomplish the task twice as fast, in 30 minutes
The function for a is (f o g) (x) = 8x^2-10.
Explanation
=========================
I already knew that the g of x is equal to
![4x^2-3](https://tex.z-dn.net/?f=4x%5E2-3)
so I substitute inside of the g of x
![g(x)=4x^2-3](https://tex.z-dn.net/?f=g%28x%29%3D4x%5E2-3)
=======>
![f(x)=4x^2-3](https://tex.z-dn.net/?f=f%28x%29%3D4x%5E2-3)
=============>
simplify it
![2(4x^2-3)-4](https://tex.z-dn.net/?f=2%284x%5E2-3%29-4)
=======>
![8x^2-6-4](https://tex.z-dn.net/?f=8x%5E2-6-4)
=========>
![8x^2-10](https://tex.z-dn.net/?f=8x%5E2-10)
Answer:
h(-2) = -1
Step-by-step explanation:
h(x)=-2x-5
Let x= -2
h(-2)=-2*-2-5
= 4 -5
h(-2) = -1